# MapsTotal and Partial Maps

*Maps*(or

*dictionaries*) are ubiquitous data structures both generally and in the theory of programming languages in particular; we're going to need them in many places in the coming chapters. They also make a nice case study using ideas we've seen in previous chapters, including building data structures out of higher-order functions (from Basics and Poly) and the use of reflection to streamline proofs (from IndProp).

*total*maps, which include a "default" element to be returned when a key being looked up doesn't exist, and

*partial*maps, which return an option to indicate success or failure. The latter is defined in terms of the former, using None as the default element.

# The Coq Standard Library

Require Import Coq.Arith.Arith.

Require Import Coq.Bool.Bool.

Require Import Coq.Strings.String.

Require Import Coq.Logic.FunctionalExtensionality.

Require Import Coq.Bool.Bool.

Require Import Coq.Strings.String.

Require Import Coq.Logic.FunctionalExtensionality.

Documentation for the standard library can be found at
http://coq.inria.fr/library/.
The Search command is a good way to look for theorems involving
objects of specific types. Take a minute now to experiment with it.

# Identifiers

Inductive id : Type :=

| Id : string → id.

Definition beq_id x y :=

match x,y with

| Id n

end.

| Id : string → id.

Definition beq_id x y :=

match x,y with

| Id n

_{1}, Id n_{2}⇒ if string_dec n_{1}n_{2}then true else falseend.

(The function string_dec comes from Coq's string library.
If you check its result type, you'll see that it does not actually
return a bool, but rather a type that looks like {x = y} + {x
≠ y}, called a sumbool, which can be thought of as an
"evidence-carrying boolean." Formally, an element of sumbool is
either a proof that two things are equal or a proof that they are
unequal, together with a tag indicating which. But for present
purposes you can think of it as just a fancy bool.)

Theorem beq_id_refl : ∀ id, true = beq_id id id.

Proof.

intros [n]. simpl. destruct (string_dec n n).

- reflexivity.

- destruct n

Qed.

intros [n]. simpl. destruct (string_dec n n).

- reflexivity.

- destruct n

_{0}. reflexivity.Qed.

The following useful property of beq_id follows from an
analogous lemma about strings:

Theorem beq_id_true_iff : ∀ x y : id,

beq_id x y = true ↔ x = y.

beq_id x y = true ↔ x = y.

Proof.

intros [n

unfold beq_id.

destruct (string_dec n

- subst. split. reflexivity. reflexivity.

- split.

+ intros contra. inversion contra.

+ intros H. inversion H. subst. destruct n. reflexivity.

Qed.

intros [n

_{1}] [n_{2}].unfold beq_id.

destruct (string_dec n

_{1}n_{2}).- subst. split. reflexivity. reflexivity.

- split.

+ intros contra. inversion contra.

+ intros H. inversion H. subst. destruct n. reflexivity.

Qed.

Similarly:

This useful variant follows just by rewriting:

# Total Maps

*functions*, rather than lists of key-value pairs, to build maps. The advantage of this representation is that it offers a more

*extensional*view of maps, where two maps that respond to queries in the same way will be represented as literally the same thing (the very same function), rather than just "equivalent" data structures. This, in turn, simplifies proofs that use maps.

*total maps*that return a default value when we look up a key that is not present in the map.

Intuitively, a total map over an element type A is just a
function that can be used to look up ids, yielding As.
The function t_empty yields an empty total map, given a default
element; this map always returns the default element when applied
to any id.

More interesting is the update function, which (as before) takes
a map m, a key x, and a value v and returns a new map that
takes x to v and takes every other key to whatever m does.

Definition t_update {A:Type} (m : total_map A)

(x : id) (v : A) :=

fun x' ⇒ if beq_id x x' then v else m x'.

(x : id) (v : A) :=

fun x' ⇒ if beq_id x x' then v else m x'.

This definition is a nice example of higher-order programming:
t_update takes a
For example, we can build a map taking ids to bools, where Id
"foo" is mapped to true and every other key is mapped to false,
like this:

*function*m and yields a new function fun x' ⇒ ... that behaves like the desired map.
This completes the definition of total maps. Note that we
don't need to define a find operation because it is just
function application!

Example update_example1 : examplemap (Id "baz") = false.

Example update_example2 : examplemap (Id "foo") = false.

Example update_example3 : examplemap (Id "quux") = false.

Example update_example4 : examplemap (Id "bar") = true.

Proof. reflexivity. Qed.

Example update_example2 : examplemap (Id "foo") = false.

Proof. reflexivity. Qed.

Example update_example3 : examplemap (Id "quux") = false.

Proof. reflexivity. Qed.

Example update_example4 : examplemap (Id "bar") = true.

Proof. reflexivity. Qed.

To use maps in later chapters, we'll need several fundamental
facts about how they behave.
Even if you don't work the following exercises, make sure
you thoroughly understand the statements of the lemmas!
(Some of the proofs require the functional extensionality axiom,
which is discussed in the Logic chapter.)

☐
#### Exercise: 1 star, optional (t_apply_empty)

First, the empty map returns its default element for all keys:#### Exercise: 2 stars, optional (t_update_eq)

Next, if we update a map m at a key x with a new value v and then look up x in the map resulting from the update, we get back v:
Lemma t_update_eq : ∀ A (m: total_map A) x v,

(t_update m x v) x = v.

Proof.

(* FILL IN HERE *) Admitted.

☐
(t_update m x v) x = v.

Proof.

(* FILL IN HERE *) Admitted.

#### Exercise: 2 stars, optional (t_update_neq)

On the other hand, if we update a map m at a key x_{1}and then look up a

*different*key x

_{2}in the resulting map, we get the same result that m would have given:

Theorem t_update_neq : ∀ (X:Type) v x

(m : total_map X),

x

(t_update m x

Proof.

(* FILL IN HERE *) Admitted.

☐
_{1}x_{2}(m : total_map X),

x

_{1}≠ x_{2}→(t_update m x

_{1}v) x_{2}= m x_{2}.Proof.

(* FILL IN HERE *) Admitted.

#### Exercise: 2 stars, optional (t_update_shadow)

If we update a map m at a key x with a value v_{1}and then update again with the same key x and another value v

_{2}, the resulting map behaves the same (gives the same result when applied to any key) as the simpler map obtained by performing just the second update on m:

Lemma t_update_shadow : ∀ A (m: total_map A) v

t_update (t_update m x v

= t_update m x v

Proof.

(* FILL IN HERE *) Admitted.

☐
_{1}v_{2}x,t_update (t_update m x v

_{1}) x v_{2}= t_update m x v

_{2}.Proof.

(* FILL IN HERE *) Admitted.

*reflection lemma*relating the equality proposition on ids with the boolean function beq_id.

#### Exercise: 2 stars, optional (beq_idP)

Use the proof of beq_natP in chapter IndProp as a template to prove the following:_{1}and x

_{2}, we can use the destruct (beq_idP x

_{1}x

_{2}) to simultaneously perform case analysis on the result of beq_id x

_{1}x

_{2}and generate hypotheses about the equality (in the sense of =) of x

_{1}and x

_{2}.

#### Exercise: 2 stars (t_update_same)

With the example in chapter IndProp as a template, use beq_idP to prove the following theorem, which states that if we update a map to assign key x the same value as it already has in m, then the result is equal to m:
Theorem t_update_same : ∀ X x (m : total_map X),

t_update m x (m x) = m.

Proof.

(* FILL IN HERE *) Admitted.

☐
t_update m x (m x) = m.

Proof.

(* FILL IN HERE *) Admitted.

#### Exercise: 3 stars, recommended (t_update_permute)

Use beq_idP to prove one final property of the update function: If we update a map m at two distinct keys, it doesn't matter in which order we do the updates.
Theorem t_update_permute : ∀ (X:Type) v

(m : total_map X),

x

(t_update (t_update m x

= (t_update (t_update m x

Proof.

(* FILL IN HERE *) Admitted.

☐
_{1}v_{2}x_{1}x_{2}(m : total_map X),

x

_{2}≠ x_{1}→(t_update (t_update m x

_{2}v_{2}) x_{1}v_{1})= (t_update (t_update m x

_{1}v_{1}) x_{2}v_{2}).Proof.

(* FILL IN HERE *) Admitted.

# Partial maps

*partial maps*on top of total maps. A partial map with elements of type A is simply a total map with elements of type option A and default element None.

Definition partial_map (A:Type) := total_map (option A).

Definition empty {A:Type} : partial_map A :=

t_empty None.

Definition update {A:Type} (m : partial_map A)

(x : id) (v : A) :=

t_update m x (Some v).

Definition empty {A:Type} : partial_map A :=

t_empty None.

Definition update {A:Type} (m : partial_map A)

(x : id) (v : A) :=

t_update m x (Some v).

We now straightforwardly lift all of the basic lemmas about total
maps to partial maps.

Lemma apply_empty : ∀ A x, @empty A x = None.

Lemma update_eq : ∀ A (m: partial_map A) x v,

(update m x v) x = Some v.

Theorem update_neq : ∀ (X:Type) v x

(m : partial_map X),

x

(update m x

Lemma update_shadow : ∀ A (m: partial_map A) v

update (update m x v

Theorem update_same : ∀ X v x (m : partial_map X),

m x = Some v →

update m x v = m.

Theorem update_permute : ∀ (X:Type) v

(m : partial_map X),

x

(update (update m x

= (update (update m x

Lemma update_eq : ∀ A (m: partial_map A) x v,

(update m x v) x = Some v.

Theorem update_neq : ∀ (X:Type) v x

_{1}x_{2}(m : partial_map X),

x

_{2}≠ x_{1}→(update m x

_{2}v) x_{1}= m x_{1}.Lemma update_shadow : ∀ A (m: partial_map A) v

_{1}v_{2}x,update (update m x v

_{1}) x v_{2}= update m x v_{2}.Theorem update_same : ∀ X v x (m : partial_map X),

m x = Some v →

update m x v = m.

Theorem update_permute : ∀ (X:Type) v

_{1}v_{2}x_{1}x_{2}(m : partial_map X),

x

_{2}≠ x_{1}→(update (update m x

_{2}v_{2}) x_{1}v_{1})= (update (update m x

_{1}v_{1}) x_{2}v_{2}).